The regulatory role of microRNAs in common eye diseases: A brief review - Benavides-Aguilar, Javier A.; Morales-Rodríguez, Jonathan I.; Ambriz-González, Héctor; Ruiz-Manriquez, Luis M.; Banerjee, Antara; Pathak, Surajit; Duttaroy, Asim K.; Paul, Sujay (Frontiers in Genetics, 2023)
MicroRNAs (miRNAs) are highly conserved, small non-coding RNA molecules (~21 nucleotides) that regulate numerous biological processes, including developmental timing, hematopoiesis, organogenesis, apoptosis, cell differentiation, and proliferation either by mRNA degradation or translation repression. Since eye physiology requires a perfect orchestration of complex regulatory networks, an altered expression of key regulatory molecules such as miRNAs potentially leads to numerous eye disorders. In recent years, comprehensive progress has been made in demonstrating the precise roles of miRNAs, emphasizing their potential use in diagnostic and therapeutic purposes of chronic human diseases. Thus, this review explicitly illustrates the regulatory roles of miRNAs in four common eye disorders, such as cataract, glaucoma, macular degeneration, and uveitis, and their application in disease management